Application of schneider M340 PLC on dynamic braking of three phase induction motor - Ferdianto Tangdililing, Ferdi; Runtono, Marcelino Rioz (Fidelity : Jurnal Teknik Elektro, 2024)
This study designs and builds a PLC application to optimize the dynamic braking process of a three-phase induction motor for safer and more efficient operation. This application monitors the motor braking system and calculates the motor braking time through a computer. The method used is experimental with the aim of designing a PLC application as a motor braking system using the dynamic braking method. The braking system utilizes PLC as the control system. To achieve dynamic braking, the stator coil of the motor receives an injection of direct current (DC) from a directed power source. In this testing, the observed variables are the injected DC current value and the duration of the injection time. The test results demonstrate that the implementation of PLC in the dynamic braking of a three-phase induction motor performs well in calculating the motor braking time and monitoring the braking process. With a DC current injection of 0,5 A in the dynamic braking test, an average stopping time of 2,63 seconds was obtained. With a DC current injection of 0,75 A in the dynamic braking test, an average stopping time of 2,13 seconds was obtained.